Exploring Trends of Web-Based Vocabulary Learning Apps in Indonesian Research: A Systematic Literature Review - Muallim, Muajiz; Mustain, Mustain; Ulfa, Siti Maria (Institut Agama Islam Negeri Palopo, 2024)
Research on web-based vocabulary learning applications has gained momentum in recent years, reflecting the growing interest in technology-enhanced education across Indonesia. However, a comprehensive understanding of how these studies have evolved and contributed to the field remains limited. This systematic review aims to analyze research trends on web-based applications for vocabulary acquisition in Indonesia from 2019 to 2024, focusing on the themes, methodologies, and outcomes reported in these studies. Following the PRISMA framework, 80 studies were identified from databases such as Semantic Scholar and Garuda. After duplicate removal and relevance screening, 42 full-text articles were reviewed, with 35 meeting the final inclusion criteria. The analysis reveals an increasing focus on platforms like Duolingo, Quipper, and Memrise, with many studies employing experimental methods to assess vocabulary improvement. Key trends include the integration of gamification and multimedia elements to enhance engagement and learner motivation. The review reveals an increasing focus on web-based vocabulary learning applications in Indonesian research from 2019 to 2024, with most studies adopting experimental designs to evaluate short-term learning outcomes. The findings highlight several applications such as Duolingo, Quipper, and Memrise are frequently employed, with positive effects on vocabulary acquisition through gamification and multimedia features. However, the research predominantly focuses on small-scale implementations, with limited studies exploring long-term impacts or usage in diverse educational contexts.